Neurosurgical procedures for children with myelomeningocele after fetal or postnatal surgery: a comparative effectiveness study. (2nd January 2021) - Worley, Gordon; Greenberg, Rachel G; Rocque, Brandon G; Liu, Tiebin; Dicianno, Brad E; Castillo, Jonathan P; Ward, Elisabeth A; Williams, Tonya R; Blount, Jeffrey P; Wiener, John S
Abstract : Aim: To compare the frequencies of neurosurgical procedures to treat comorbid conditions of myelomeningocele in patients who underwent fetal surgery versus postnatal surgery for closure of the placode. Method: By utilizing the National Spina Bifida Patient Registry in a comparative effectiveness study, 298 fetal surgery patients were matched by birthdate (±3mo) and spina bifida clinic site with one to three postnatal surgery patients ( n =648). Histories were obtained by record review on enrollment and yearly subsequently. Multivariable Poisson regression was used to compare frequencies of procedures between cohorts, with adjustments for sex, ethnicity, insurance status, spinal segmental level of motor function, age at last visit recorded in the Registry, and, for shunt revision in shunted patients, age at cerebrospinal fluid (CSF) diversion. Results: The median age at last visit was 4 years. In fully adjusted analyses in patients aged at least 12 months old, fetal surgery was associated with decreased frequency of CSF diversion for hydrocephalus by ventriculoperitoneal shunt insertion or endoscopic third ventriculostomy compared with postnatal surgery (46% vs 79%; incidence rate ratio=0.61; 95% confidence interval [CI] 0.53–0.71; p <0.01). Over all ages, fetal surgery was associated with decreased frequency of Chiari decompression for brainstem dysfunction (3% vs 7%; incidence rate ratio=0.41; 95% CI 0.19–0.88; p =0.02). Also over all ages, differences were not significant in frequencies of shunt revision in shunted patients (53% vs 55%; incidence rate ratio=0.87; 95% CI 0.69–1.11; p =0.27), nor tethered cord release for acquired spinal cord dysfunction (18% vs 16%; incidence rate ratio=1.11; 95% CI 0.84–1.47; p =0.46). Interpretation: Even with the variations inherent in clinical practice, fetal surgery was associated with lower frequencies of CSF diversion and of Chiari decompression, independent of covariates. What this paper adds Fetal surgery was associated with lower frequencies of cerebrospinal fluid diversion and decompression of Chiari II malformation than postnatal surgery. Frequencies of ventriculoperitoneal shunt revision and tethered cord release were not significantly different between cohorts. What this paper adds: Fetal surgery was associated with lower frequencies of cerebrospinal fluid diversion and decompression of Chiari II malformation than postnatal surgery. Frequencies of ventriculoperitoneal shunt revision and tethered cord release were not significantly different between cohorts. This original article is commented by Joyeux and Belfort on page 1243 of this issue.